Prevalence of sleep-disordered breathing related to malocclusion in children (Research, Society and Development, 2021)
Sleep-disordered breathing is characterized by airway dysfunction that can occur in any age, but most prevalent in children, caused by the occurrence of respiratory effort, snoring or even by  apnea during sleep. Therefore, the aim of this study was to survey the prevalence of sleep disorders associated with malocclusion in children aged 3 to 12 years in Mineiros, State of Goiás, Brazil. Material and Methods: this is a field research with a sample of 99 children affected by some type of sleep-disordered breathing and malocclusions. Data were collected through a questionnaire about sleep-disordered breathing and a clinical record carried out through intraoral clinical examination. Results: among the 24 children with SDB, 17 had SDB and Malocclusion, which is 70.8% of the children had SDB associated with malocclusion. Of the 75 children without SDB, 11 (14.7%) had malocclusion. Conclusion: No significant differences were found between sleep-disordered breathing and sex-related malocclusions.